2017
DOI: 10.1242/jcs.196907
|View full text |Cite
|
Sign up to set email alerts
|

MCSF orchestrates branching morphogenesis in developing submandibular gland tissue

Abstract: The importance of macrophages in tissue development and regeneration has been strongly emphasized. However, the specific roles of macrophage colony-stimulating factor (MCSF), the key regulator of macrophage differentiation, in glandular tissue development have been unexplored. Here, we disclose new macrophage-independent roles of MCSF in tissue development. We initially found that MCSF is markedly upregulated at embryonic day (E)13.5, at a stage preceding the colonization of macrophages (at E15.5), in mouse su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Therefore, CD11c − macrophages may play an essential role in gland morphogenesis in association with the ductal region in fetal SGs. The treatment of SMGs isolated from E12.5 mouse embryos with anti-CSF-1 or anti-CSF-1R reduced the numbers of F4/80 + macrophages and suppressed the development of SMGs; however, the latter effect may be explained by macrophage-independent pathways 43 . The specific depletion of macrophages by novel approaches, such as the use of CD64-diphtheria toxin receptor mice, may contribute to a more detailed understanding of the exact role of macrophages in SG morphogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, CD11c − macrophages may play an essential role in gland morphogenesis in association with the ductal region in fetal SGs. The treatment of SMGs isolated from E12.5 mouse embryos with anti-CSF-1 or anti-CSF-1R reduced the numbers of F4/80 + macrophages and suppressed the development of SMGs; however, the latter effect may be explained by macrophage-independent pathways 43 . The specific depletion of macrophages by novel approaches, such as the use of CD64-diphtheria toxin receptor mice, may contribute to a more detailed understanding of the exact role of macrophages in SG morphogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…While numerous reviews have detailed the functions of kidney macrophages in the healthy and diseased adult kidney (Rogers et al, 2014 ; Cao et al, 2015 ; Guiteras et al, 2016 ), there are few descriptions of the functions of kidney macrophages in renal development. In other developing organs, macrophages are critical in processes such as branching morphogenesis, angiogenesis, and the clearance of dead cells (Gouon-Evans et al, 2000 ; Kawane et al, 2003 ; Pollard, 2009 ; DeFalco et al, 2014 ; Sathi et al, 2017 ). It is now becoming clear that these processes are also facilitated by kidney macrophages during renal organogenesis.…”
Section: Functions Of Macrophages In Kidney Developmentmentioning
confidence: 99%
“…Macrophages contribute to branching morphogenesis in the developing lung, mammary gland, and submandibular gland (Gouon-Evans et al, 2000 ; Pollard, 2009 ; Jones et al, 2013 ; Sathi et al, 2017 ). Evidence suggests that kidney macrophages similarly contribute to ureteric bud branching in the kidney (Rae et al, 2007 ; Muthukrishnan et al, 2017 ).…”
Section: Ureteric Bud Branching Morphogenesismentioning
confidence: 99%
“…32 An alternative mechanism involves "cell competition," which is a prevalent feature in epithelial tissues. 34 Previous reports regarding salivary branching identified FN as a key regulator of cleft formation. Therefore, cells of the inner buds will be surpassed in growth rate by the outer buds' cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this optimized model provided an excellent platform for salivary gland regeneration essays as we showed in our recently published report. 34 Previous reports regarding salivary branching identified FN as a key regulator of cleft formation. 11 However, reports about other glandular tissues branching suggested that FN played a wider role in branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%